Impactos ambientais da mineração de argila para cerâmica vermelha na sub-bacia do Ribeirão Jacutinga - Rio Claro E Corumbataí (SP) - Scalco, Jheynne Pereira [UNESP]; Ferreira, Gilda Carneiro [UNESP] (My University, 2013)
The knowledge of some of the aspects of environmental impacts made by a determinated activity on a local scale is a very important tool to discuss about the relationship between humans and nature. Many environmental problems are the result of ignorance about the limits of the physical mean causing misuse of those resources. This research aims to characterize the impacts of mining of 10 producers located in Ribeirão Jacutinga watershed. The small mining of raw material (clay) from Corumbataí formation causes impacts in this sub-basin and the region for a long term. It was Geographic Information System for analysis of satellite images (Landsat-TM) and data obtained on the cartographic basis (scale 1:10.000) as means of impact characterization. The main impacts identified were related to mining activities: open pits in lowland sites, lake formation in abandoned pits, changes in the landscape, lack of actions for recovery of mined areas, cutting of native forest in previous years. Also was identified greater environmental fragility in the watershed, which is associated with areas of greater slope or the extraction sites. Mineral exploration has brought significant changes in the natural environmental of this sub-basin; hence the importance of knowing more about environmental limitations. Moreover is important the development of technologies that allow impact management. This study concludes that it is very important to respect the limits imposed by the physical environment and valuing sustainable activities.
Environmental impacts of mining for pottery red clay in sub-basin Ribeirão Jacutinga - Rio Claro E Corumbataí (SP)
Keywords: Clay mining; Environmental impact; Watershed